THE EFFECT OF LAVENDER AROMATHERAPY ON SLEEP DISORDERS IN THE ELDERLY - Kolompoy, Jane Annita; Runtu, Lorrien Grace; Indar, Maaku Fauziah Puspita (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: Sleep disturbance or insomnia is one of the most common disorders in the elderly. To overcome insomnia can be multiple ways a treatment such as in the form of non-pharmacological that is by using a provision of lavender aromatherapy. Objective: This study aims to determine the effect of lavender aroma therapy on the sleep quality of the elderly. Methods: this study uses a type of literature review research using the results of previous research, textbooks or research journals. To obtain data that is in accordance with the topic of discussion the researcher conducts national and international-based journal searches on two databases PUBMED and google scholar using the keyword lavender aromatherapy, insomnia, elderly. The keywords used are listed in each journal title that is obtained with the provisions of the journal you are looking for, namely from 2016-2020 then the journals that can be selected and the researcher determine 6 journals that are in accordance with the topic of the literature review discussion. Results: Based on 6 literature reviews, the results of the study stated that there was an effect of giving lavender aromatherapy before going to bed on reducing sleep disorders in the elderly. With various interventions, namely by placing aromatherapy on a cotton ball, handkerchief, inhaling through steam. The duration of administration depends on the level of insomnia in the elderly. The average duration of administration is 30 minutes, while the duration of intervention is 5-21 days depending on the level of insomnia in the elderly. Conclusion: There is an effect of lavender aromatherapy on sleep disorders in the elderly